Planejamento florestal aplicado ao setor da fumicultura no Sul do Brasil - Souza, Pabulo Diogo de (2019)
The tobacco sector is composed of activities of national social and economic importance. Virginia tobacco is one of the highest value-added tobacco varieties, among those grown in southern Brazil. After harvest, this variety is submitted to drying in curing units, which require energy for its operation and have as main energy source the combustion of firewood from Eucalyptus spp. The tobacco sector lacks studies aimed at the forest production capacity of its afforestation, which generates uncertainties regarding the supply. In this sense, the objective of this study was to analyze the production capacity of the forest base of tobacco cultivation in the South of Brazil, in response to the demand for firewood in the process of curing tobacco Virginia. The work was carried out in the states of Paraná, Santa Catarina and Rio Grande do Sul, and the study area was composed of Eucalyptus spp. existing on small farms distributed in seven Virginia tobacco producing regions. Initially, it was estimated the area of the forest base of the tobacco sector, considering the 7 regions (PR - Southeast Paranaense, SC - Planalto Norte, SC - Alto Vale, SC - Southern Litoral, RS - Centro Serra, RS - Depression Central and RS - Costa Doce). From a single-occasion forest inventory database, the structure of the forest base in the sector was estimated. Through consultations with the database of the Brazilian Tobacco Growers Association, estimates were made of Virginia tobacco production for each of the 7 regions. After that, wood production and consumption scenarios were built. The scenarios consisted of the relationship between the variables existing forest area and forest production estimated at 7 years, and the variables forest area and wood consumption needed to obtain energy sufficiency in the curing process, considering consumption means in conventional curing units (scenario 1) and forced air curing units (scenario 2). Simulations of wood production and consumption were carried out in a planning horizon of 21 years, from the application of the volume regulation method. Finally, the estimation of the forest area required by small rural property was obtained to obtain the energy sufficiency in scenarios 1 and 2 for each region. The 7 regions, respectively, consume in scenario 1 and 2, 3.674.637,60 m³ and 2.482.334,98 m³ of firewood per year. In the PR - Southeastern region of Paraná, the estimated wood production was insufficient to supply the demand for firewood to cure tobacco in both scenarios. The regions of Santa Catarina were sufficient in energy only when considered scenario 2. In the State of Rio Grande do Sul, the central region Serra - RS and Central Depression were insufficient in energy regardless of the scenario considered. On the other hand, the Costa Doce-RS region presented energy sufficiency in both scenarios. In general, it has been observed that the forest base of the tobacco sector in southern Brazil is insufficient to promote energy sufficiency in the Virginia tobacco cure process.